Current and Future Applications of Carbon Nanotubes in Flexible Electronics - Gu, Fanchen (Transactions on Computer Science and Intelligent Systems Research, 2025)
With the rapid development of wearable devices, smart medical and other industries, traditional rigid electronic materials are difficult to meet the requirements of modern electronic devices for flexibility and stability. Carbon nanotubes have become an ideal material for flexible electronic devices due to their unique performance characteristics. This paper focuses on the preparation and processing technologies of carbon nanotube flexible electronic materials, including the floating catalyst chemical vapour deposition method, solution method processing and selective deposition, dry transfer and orientation alignment, and other advanced technologies. It analyses the advantages and limitations of various technologies. Meanwhile, this study discusses in detail the specific applications of carbon nanotubes in three major fields, namely, flexible thin film transistors and logic circuits, flexible transparent electrodes, and multifunctional flexible sensors, demonstrating their potential for practical engineering applications. However, the technology still faces challenges such as difficult process control, complex processing, and insufficient long-term stability, which constrain its industrialisation. This study provides a systematic theoretical guidance and technical reference for the development of carbon nanotube flexible electronics, which is of great value in promoting the innovation and application of next-generation flexible electronic devices.
Keywords: Carbon nanotubes; Flexible electronics; Wearable sensors.